2007
DOI: 10.1002/jcb.21213
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma: A prototypic disease model for the characterization and therapeutic targeting of interactions between tumor cells and their local microenvironment

Abstract: The interaction between tumor cells and the local milieu where are homing has recently become the focus of extensive research in a broad range of malignancies. Among them, multiple myeloma (MM) is now recognized as a prototypical tumor model for the characterization of these interactions. This is due not only to the propensity of MM cells to target the skeleton and form lytic bone lesions, but because interactions of MM cells with normal cells of the bone milieu can attenuate the anti-tumor activity of convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 167 publications
1
74
0
Order By: Relevance
“…In cooperation with the driving tumorigenic effects of genetic lesions within MM cells, the BM microenvironment provides essential support to the propagation and expansion of malignant clones and promotes drug resistance [8,26,32]. However, the RPI-1 ability to abrogate KMS18 cell growth enhancement provided by aFGF, suggests a potential benefit extended to t(4;14) MM not expressing a constitutively active FGFR3.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In cooperation with the driving tumorigenic effects of genetic lesions within MM cells, the BM microenvironment provides essential support to the propagation and expansion of malignant clones and promotes drug resistance [8,26,32]. However, the RPI-1 ability to abrogate KMS18 cell growth enhancement provided by aFGF, suggests a potential benefit extended to t(4;14) MM not expressing a constitutively active FGFR3.…”
Section: Discussionmentioning
confidence: 99%
“…The potential therapeutic relevance of JAK2 in the treatment of MM is well recognized and related to its role as an effector of the signaling cascade induced by IL-6, a major growth and anti-apoptotic factor implicated in both autocrine and paracrine MM cell stimulation within the BM milieu [8,12,41]. It has been reported that IL-6 also participate to the regulation of BCMA expression [42], thus the early and stable downregulation of this receptor detected in KMS11 cells after RPI- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 18 even in untreated cells, the expression of alternatively spliced forms of Mcl-1 cannot be ruled out [48].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations